PENGARUH SUPERVISI KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMK N 2 BATAM - Dhenny Asmarazisa (BENING, 2018)
This study aimed to determine the effect of the principal supervision and motivation to work on teachers performance, both separately (partial) or jointly (Simultaneously) that conducted at SMK Negeri 2 Batam.In this study, 80 teachers were used for sampling that taken from total populations (teachers). While the types of data used from the questionnaires were distributed throughout the samples. Data analysis was performed by descriptive statistics, which were used to describes in providing images of the object under study through the samples or populations of data obtained in the field associated with the relevant theories and techniques of quantitative analysis of the data which was given a score according to the scale of measurement and to test results using SPSS (Statistics Product and Service Solutions).The result of the research conclude that the partial supervision principals (X1) is not positive and significant effect on teacher performance (Y), with test results of 0.643 or 64.3%, while work motivation (X2) and a significant positive effect on teacher performance (Y) as seen from the test results of 0.37 or 3.7%. But simultaneously the principal supervision and motivation positive and significant impact on the performance of the teacher of SMK Negeri 2 Batam Closeness of 0.567 or 56.7% while the remaining amount of 0.433 or 43.3% is influenced by other variables or factors.Keywords: Supervision, Work Motivation, Performance.